Analysis on Technical Efficiency and Influencing Factors of Agricultural Production in China —— Based on the Stochastic Frontier Analysis model - Huang Weiwei; Xu Liwenjun; Guo Yinru (E3S Web of Conferences, 2021)
This paper selects the panel data on 31 provinces (cities) in China, from 2007 to 2017, and uses Stochastic Frontier Analysis Model to measure the efficiency of technical efficiency and influencing factors of agricultural production in China. The research shows that from 2007 to 2017, China’s agricultural average production technology efficiency has steadily improved, but there is still much room for development. The agricultural production technology efficiency is greatly different in different part of China. The eastern region has the highest efficiency, and the central and western regions are lower than the national average. Labor input, fertilizer application, and diesel fuel are factors that directly affect the technical efficiency of agricultural output. Time trend and urbanization level indirectly affect the agricultural production technology efficiency, and the impact is positive.